Methodological problems in the study of African traditional religions - Adogbo, Michael P (Journal of Theology for Southern Africa, 2005)
This essay examines some of the methodological paradigms used by scholars in the study of African Traditional Religions. After providing a critique of some of the key approaches of the past for their failure to respect the heterogeneity of African Traditional Religions, the essay proposes a 'macro-theory' which brings together thematic, descriptive and historical approaches with a focus on beliefs and practices.
Keywords: Africa – Religion – Study and teaching; Religions – Study and teaching – Methodology